2008
DOI: 10.1007/s00216-008-1926-y
|View full text |Cite
|
Sign up to set email alerts
|

Spectrochemical analysis of powder using 355 nm Nd-YAG laser-induced low-pressure plasma

Abstract: The applicability of spectrochemical analysis of minute amounts of powder samples was investigated using an ultraviolet Nd-YAG laser (355 nm) and low-pressure ambient air. A large variety of chemical powder samples of different composition were employed in the experiment. These included a mixture of copper(II) sulfate pentahydrate, zinc sulfide, and chromium(III) sulfate n-hydrate powders, baby powder, cosmetic powders, gold films, zinc supplement tablet, and muds and soils from different areas. The powder sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…It is known that low-cost gold foils containing silver (Ag) and copper (Cu) as impurities are also available on the market because of the high cost of high-purity gold foil. 13 Using this technique, we confirmed that the impurity emission lines of both Ag and Cu in high-purity gold foil are greatly suppressed, as shown in Fig. 7b.…”
Section: Resultssupporting
confidence: 67%
“…It is known that low-cost gold foils containing silver (Ag) and copper (Cu) as impurities are also available on the market because of the high cost of high-purity gold foil. 13 Using this technique, we confirmed that the impurity emission lines of both Ag and Cu in high-purity gold foil are greatly suppressed, as shown in Fig. 7b.…”
Section: Resultssupporting
confidence: 67%
“…Further measurement on a number of the standard soil samples of various Pb contents were shown to yield a linear calibration line with practically zero intercept and a detection limit of < 10 ppm. Despite the favorable results reported in the previous studies [19,20], the generation of shock wave plasma was only indicated by the plasma emission characteristics, leaving its direct detection and the underlying plasma excitation mechanism less than appropriately addressed.…”
Section: Introductionmentioning
confidence: 88%
“…The resulted spectra is presented in Fig. 5, (a 19 for the low pressure and atmospheric pressure He gases. One may therefore assumed the existence of local thermal equillibrium (LTE) condition for the application of the two-lines method.…”
Section: Excitation Mechanism Of the Powder Sample Plasmamentioning
confidence: 99%
See 1 more Smart Citation
“…There are several procedures commonly used for this purpose: (i) fusion with lithium borate; [9][10][11] (ii) the use of methacrylate glue; 12 (iii) the use of a sol-gel technique; 13 (iv) pellet formation by means of manual pellet press; 4,14-20 and (v) trapping powdered sample in the tiny microholes on the quartz target. 21 The common step of all those procedures is grounding and homogenizing of the solid sample. The differences lie in the type of binder used for powder immobilization, the need to press the target, time of sample preparation and the long-term stability of the obtained target.…”
Section: Introductionmentioning
confidence: 99%